Calculus in Several Variables. Interactive Visualization (Wolfram CDPlayer) 2nd Ed.: Cálculo en Varias Variables. Visualización interactiva - Mora Flores, Walter (Revista Digital: Matemática, Educación e Internet, 2019)
The goal of this book is interactive visualization in 2D and 3D. Most graphics come with a link to an application, usually called a "demo" (interactive application), that runs with Wolfram CDFPlayer (free). The "interactive applications" are a .cdf file that runs with Wolfram CDFPlayer and require that you have installed this Wolfram CDFPlayer application on your computer. The application is free. This is a new edition where the cdf applications have been optimized and two chapters have been added: Vectors, Straights and Planes (and also polar coordinates), Parameterization and Vector Functions. Many of the examples and exercises of this book have appeared in exams, in the course of Superior Calculation of the Technological Institute of Costa Rica. The reader can visualize the theory and many of the examples, and interact with the figures in the interactive application, using the mouse. The idea is to visualize not only the three-dimensional space, but also to be able to train in visualizing surface cuts, intersections and projections of a surface or a solid, in some of the planes XY; XZ or YZ. This knowledge is then applied in the calculation of double, triple, line and surface integrals. Various interactive applications are used to visualize the dynamics of a definition or theorem and its scope and meaning. As it is known, interactive visualization works well as a complement and requires "narrative" on the part of the teacher in order to obtain good teaching results. Verbalization exercises, in some activities, by the student are also desirable.